2015
DOI: 10.5219/429
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of meat quality after application of different feed additives in diet of broiler chickens

Abstract: The present study was conducted to investigate the effect of natural feed additives, namely bee pollen extract, propolis extract and probiotic preparation, on technological properties of meat in order to evaluate the meat quality of Ross 308 broiler chickens.  The feeding of chickens (180 pcs) lasted for a period of 42 days. The experiment was carried out without segregation between the genders. The chickens were randomly divided into 4 groups. The control group was fed a basal diet, whereas the other three gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 44 publications
2
7
1
Order By: Relevance
“…In the present study, the leg muscle lightness (L∗), redness (a∗), and yellowness (b∗) were significantly increased in the probiotic-supplemented groups compared with controls. Similar findings ( Wideman et al., 2016 ; Khan et al., 2018 ) and conflicting results ( Haščík et al., 2015 ; Stęczny and Kokoszynski, 2019 ) have been reported previously. The improvement in the leg muscle color revealed in the present study may attribute similarly to the findings in pigs ( Han et al., 2020 ).…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, the leg muscle lightness (L∗), redness (a∗), and yellowness (b∗) were significantly increased in the probiotic-supplemented groups compared with controls. Similar findings ( Wideman et al., 2016 ; Khan et al., 2018 ) and conflicting results ( Haščík et al., 2015 ; Stęczny and Kokoszynski, 2019 ) have been reported previously. The improvement in the leg muscle color revealed in the present study may attribute similarly to the findings in pigs ( Han et al., 2020 ).…”
Section: Discussionsupporting
confidence: 90%
“…(2015a) mentioned that redness in breast muscle was increased, whereas the values of L∗ and b∗ for broiler breast meat were not altered because of probiotic ( Lactobacillus fermentum ) supplementation to drinking water. However, Haščík et al. (2015b) found a significant increase in redness and yellowness of thigh and increase in the lightness of breast and thigh cuts in birds fed probiotics alone or in combination with pollen.…”
Section: Discussionmentioning
confidence: 87%
“…Various trials showed that silymarin addition in diet or silymarin administration increased productive and reproductive performances and improved livestock health status of animals (Tedesco, 2001). Many works investigate the effect of herbs addition to feed mixtures for broiler chickens and their influence to the meat quality (Haščík et al, 2015;Bobko et al, 2009). The rapid growth of modern broilers hybrid and toxic substances in the feed mixtures can lead to metabolic and oxidative stress.…”
Section: Introductionmentioning
confidence: 99%